2022
DOI: 10.1007/s40120-022-00333-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Training with a Brain–Computer Interface-Controlled Robot on Rehabilitation Outcome in Patients with Subacute Stroke: A Randomized Controlled Trial

Abstract: Introduction: Stroke is always associated with a difficult functional recovery process. A brain-computer interface (BCI) is a technology which provides a direct connection between the human brain and external devices. The primary aim of this study was to determine whether training with a BCI-controlled robot can improve functions in patients with subacute stroke. Methods: Subacute stroke patients aged 32--68 years with a course of 2 weeks to 3 months were randomly assigned to the BCI group or to the sham group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Most of the included studies didn't report any adverse effect during trials. Ten of the studies reported that no serious adverse effects were found in the participants during and after BCI training or intervention s [13,14,24,28,31,38,42,45,50,52].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Most of the included studies didn't report any adverse effect during trials. Ten of the studies reported that no serious adverse effects were found in the participants during and after BCI training or intervention s [13,14,24,28,31,38,42,45,50,52].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…There is no best recommendation for CPC therapy. The combination therapy schemes used in animal experiments and clinical trials can be divided into the following categories: central intervention combined with conventional rehabilitation therapy, NMES, TOT, use of a rehabilitation robot, or acupuncture (Li et al, 2018;Xu et al, 2018;Zhao et al, 2022). These findings provide the evidence and potential of the CPC closed-loop theory.…”
Section: Application Of Central-peripheral-central Closed-loop Rehabi...mentioning
confidence: 99%
“…It is an actively evoked EEG signal that has high application values in the field of neurorehabilitation because it can independently elicit potential activity in motorrelated brain regions without external stimulation (Pfurtscheller and Neuper, 2001). The MI-BCI detects the user's motor intentions by capturing the potential changes, and the output command could be used to control functional electrical stimulation (FES), exoskeletons, or other rehabilitation assistive equipment (Biasiucci et al, 2018;Zhao et al, 2022). Thus MI-BCI is valuable in the medical rehabilitation pathway for patients with motor dysfunction through the provision of active rehabilitation training (Jeong et al, 2019;Romero-Laiseca et al, 2020).…”
Section: Introductionmentioning
confidence: 99%